Estimates of the Danish general government budget balance and the cyclical budget volatility 1875-2003 - Kim Abildgren (Danmarks Nationalbank, 2005)
The paper presents time series for Danish general government net lending in the period 1875-2003 and analyses the long-term term fiscal development in Denmark. Even though Denmark today has one of the largest public sectors in Europe, relatively speaking, the Danish general government's deficit has only significantly exceeded 3 per cent of GDP during World War II and in the early 1980s. Furthermore, the cyclical impact on the general government budget balance seems most often to be relatively modest compared to that of discretionary fiscalpolicy changes. However, calculations on the cyclical budget volatility also seem to suggest that the cyclically adjusted budget balance has to be in surplus in periods with strong economic growth if the automatic stabilisers should be allowed to work freely during a cyclical downturn without violating a 3-per-cent budget criteria (the reference value in the Maastricht Treaty).
Keywords: E32; E62; N23; N24; 330; historical statistics; cyclical adjustment; government budget; business cycles; fiscal policy; Maastricht Treaty; Öffentlicher Haushalt; Finanzpolitik; Konjunktur; Dänemark; Europäischer Stabilitätsmechanismus